Cobalt bis(acetylacetonate)–tert-butyl hydroperoxide–triethylsilane: a general reagent combination for the Markovnikov-selective hydrofunctionalization of alkenes by hydrogen atom transfer - Ma, Xiaoshen; Herzon, Seth B. (Beilstein Journal of Organic Chemistry, 2018)
We show that cobalt bis(acetylacetonate) [Co(acac)2], tert-butyl hydroperoxide (TBHP), and triethylsilane (Et3SiH) constitute an inexpensive, general, and practical reagent combination to initiate a broad range of Markovnikov-selective alkene hydrofunctionalization reactions. These transformations are believed to proceed by cobalt-mediated hydrogen atom transfer (HAT) to the alkene substrate, followed by interception of the resulting alkyl radical intermediate with a SOMOphile. In addition, we report the first reductive couplings of unactivated alkenes and aryldiazonium salts by an HAT pathway. The simplicity and generality of the Co(acac)2–TBHP–Et3SiH reagent combination suggests it as a useful starting point to develop HAT reactions in complex settings.
Keywords: HAT; hydrogen atom transfer; hydrofunctionalization